3D Modeling and functional analysis of a Spanish historical invention of the nineteenth century for mineral extraction: The Emilina Machine (2015)
In this paper, we analyze in detail a Spanish historical nineteenth-century invention used for mineral extraction: the Emilina machine. In particular, three-dimensional modeling is performed using software parametric (CATIA v5) of each of the elements of the set. Also, after obtaining the 3D model, a functional analysis using techniques of Computer Aided Engineering has been performed, based on the analysis of the von Mises stress and displacement, ensuring that the highest stress concentrations occur in the principal axis, the radii of the pulleys, the upper cable of the main drum, the connection between the secondary shaft and the main drum and the wood support structure, and that the highest concentration of displacements on the steering wheel of the steam machine, in the main shaft on which it is coupled and in the pulleys.